A tertiary care centre profile of heart diseases among diagnosed cases of chronic kidney disease - Bakhtar, Vijay; Bakhtar, Niyati; Pandey, Neha; Bakhtar, Nikhil (International Journal of Research in Medical Sciences, 2020)
Background: Chronic Kidney Disease (CKD) is a risk factor for development of cardiovascular diseases. Cardiovascular diseases are the predominant cause of morbidity and mortality in patients with CKD. There is limited data on cardiovascular diseases among CKD patients from developing countries including India. With the present study, the prevalence and patterns of cardiac diseases among patients with CKD were profiled. Methods: This was a cross sectional study in which 217 patients with CKD were studied over a period of two years and six months. Data on demographic characteristics and risk factors for cardiovascular diseases were collected using a standardized questionnaire. Cardiac evaluation was done using resting ECG and echocardiography. Results: One hundred eighteen (54.4%) patients had either eccentric or concentric LVH. Patients with LVH were more likely to be hypertensive (p<0.001) or anemic (p=0.034). Up to 9.2% of study subjects had valvular heart disease (rheumatic or degenerative) and 22% had pericarditis. Patients with pericarditis were more likely to have a serum urea concentration greater than 60mg/dl (p=0.327). Forty-one patients (18.9%) had left ventricular systolic failure (EF<50%). There was a statistically insignificant higher prevalence of systolic failure in patients with LVH (21% vs. 16%), (p=0.346). Thirty-eight participants (17.5%) had diastolic failure while 2% had cardiac rhythm abnormalities. Conclusions: Cardiac abnormalities are common in a relatively young Indian population with CKD. Clinicians should routinely screen and manage cardiovascular disease in CKD patients.